2022
DOI: 10.1007/s11469-021-00742-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of an Instrument to Assess the Fear of COVID-19 in a Sample in Argentina: a Mixed Approach

Abstract: The FCV-19S was the first instrument designed to assess the severity of fear related to COVID-19 and has already been validated in many languages. The objective of this study was to evaluate the homogeneity and construct validity of the 5-item version of the FCV19S, using an online questionnaire in 599 people. The participants’ age ranged from 18 to 65 years. Age, gender, marital status, educational level, employment status, and socioeconomic status were analyzed. In the evaluation process we assessed interite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…In our study, the higher educational level was significantly associated with fear of COVID-19. The impact of education on fear is controversial since two studies [ 50 , 51 ] in Peru and Iran found a positive relationship between age and fear, while two studies [ 52 , 53 ] in China and Colombia found the opposite result. Interestingly, a large study with 14,558 participants in 48 countries found that less educated participants experienced increased fear of COVID-19 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the higher educational level was significantly associated with fear of COVID-19. The impact of education on fear is controversial since two studies [ 50 , 51 ] in Peru and Iran found a positive relationship between age and fear, while two studies [ 52 , 53 ] in China and Colombia found the opposite result. Interestingly, a large study with 14,558 participants in 48 countries found that less educated participants experienced increased fear of COVID-19 [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the COVID-19 pandemic, it has posed a threat to both physical ( 1 4 ) and psychological health ( 5 14 ). This impact, coupled with its effects on social and economic aspects, has had far-reaching consequences on the safety and overall well-being of the population ( 15 , 16 ). The severity ( 2 , 17 ) and high transmission rate of COVID-19 ( 18 , 19 ) have instilled fear in people ( 15 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…This impact, coupled with its effects on social and economic aspects, has had far-reaching consequences on the safety and overall well-being of the population ( 15 , 16 ). The severity ( 2 , 17 ) and high transmission rate of COVID-19 ( 18 , 19 ) have instilled fear in people ( 15 , 20 ). This fear is exacerbated by misinformation, leading to the psychological impact of concerns about infection and the potential to infect loved ones ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since its outbreak, COVID-19 has represented a threat to physical (1-4) and psychological health (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), which, together with its impact on the social and economic level, has had repercussions on the safety and well-being of the population (15,16). The severity (2,17) and high transmission rate of COVID-19 (18,19) has created fear in people (15,20), who, by being misinformed, have suffered the psychological impact due to the concern of becoming infected and infecting their loved ones (20,21). A total of 30.5-41.8% of fear of COVID-19 in various populations has been estimated (22,23), even a study conducted in Peruvian policemen found that 42.5% were afraid of COVID-19 (24).…”
Section: Introductionmentioning
confidence: 99%